Assessing global resource use and greenhouse emissions to 2050, with ambitious resource efficiency and climate mitigation policies. (15th February 2017) - Hatfield-Dodds, Steve; Schandl, Heinz; Newth, David; Obersteiner, Michael; Cai, Yiyong; Baynes, Tim; West, James; Havlik, Petr
Abstract: Achieving sustainable development requires the decoupling of natural resource use and environmental pressures from economic growth and improvements in living standards. G7 leaders and others have called for improved resource efficiency, along with inclusive economic growth and deep cuts in global greenhouse emissions. However, the outlooks for and interactions between global natural resource use, resource efficiency, economic growth and greenhouse emissions are not well understood. We use a novel multi-regional modeling framework to develop projections to 2050 under existing trends and three policy scenarios. We find that resource efficiency could provide pro-growth pro-environment policies with global benefits of USD $2.4 trillion in 2050, and ease the politics of shifting towards sustainability. Under existing trends, resource extraction is projected to increase 119% from 2015 to 2050, from 84 to 184 billion tonnes per annum, while greenhouse gas emissions increase 41%, both driven by the value of global economic activity more than doubling. Resource efficiency and greenhouse abatement slow the growth of global resource extraction, so that in 2050 it is up to 28% lower than in existing trends. Resource efficiency reduces greenhouse gas emissions by 15–20% in 2050, with global emissions falling to 63% below 2015 levels when combined with a 2 °C emissions pathway. In contrast to greenhouse abatement, resource efficiency boosts near-term economic growth. These economic gains more than offset the near-term costs of shifting to a 2 °C emissions pathway, resulting in emissions in 2050 well below current levels, slower growth in resource extractions, and faster economic growth.